2013
DOI: 10.2319/082012-669.1
|View full text |Cite
|
Sign up to set email alerts
|

CBCT of skeletal changes following rapid maxillary expansion to increase arch-length with a development-dependent bonded or banded appliance

Abstract: Objective: To assess the three-dimensional (3D) skeletal response to a standardized 5 mm of rapid maxillary expansion (RME) in growing children (6-15 years) with maxillary width deficiency and crowding. Materials and Methods: A bonded appliance was used prior to the eruption of the maxillary first premolars (Mx4s), and a banded appliance was used thereafter. A consecutive sample of 89 patients (29 boys and 60 girls) from a large pediatric dentistry and orthodontics practice was divided into four groups: 1) 6-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
5
31
0
1
Order By: Relevance
“…(3)(4)(5)(6) Other in-vitro studies revealed the same results regarding nasal cavity widening specially the anterior and inferior parts. (7)(8)(9) Also the nasopharynx has expanded significantly as a result of inferio-anterior displacement of palatal shelves.…”
Section: Discussionsupporting
confidence: 61%
“…(3)(4)(5)(6) Other in-vitro studies revealed the same results regarding nasal cavity widening specially the anterior and inferior parts. (7)(8)(9) Also the nasopharynx has expanded significantly as a result of inferio-anterior displacement of palatal shelves.…”
Section: Discussionsupporting
confidence: 61%
“…Pertinent studies became available following the introduction of CBCT to dentistry-and orthodontics [38]-in the late 1990s [52]. More recently, systematic reviews of CBCT studies on RME have become available [5,9,21,27,37,39,[57][58][59]. Given the natural advantages of CBCT, these studies have mainly reported on changes in the transverse plane, but maxillary movements in caudal and anterior directions have also been described [27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with facial or nasal deformities and those younger than 11 years or older than 15 years were excluded from the study. Sample size was calculated based on data available in the literature, 4 and analysis was performed with G*Power Version 3.0.10 (Franz Faul, Universitä t Kiel, Germany) software. Based on a 1:1 ratio among groups, a total sample size of 42 was predicted to provide more than 80% confidence to detect differences at an a 5 .05 significance level.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] These appliances produce both orthopedic and orthodontic effects by tipping the posterior teeth buccally and enable dental extrusion and lateral rotations of the alveolar segments. [4][5][6] These effects of RME cause downward and backward rotation of the mandible and increased facial height. 2,7,8 In orthodontic evaluation, the most common ways to determine the soft tissue effects of the treatment are soft tissue analysis of the patient's cephalometric radiographs and photographs.…”
Section: Introductionmentioning
confidence: 99%